THE IMPORTANCE OF INTERDISCIPLINARY INTEGRATION IN EDUCATION - J. Kholmatov (Journal of new century innovations, 2024)
Annotation: This article explores the significance of interdisciplinary integration in modern education. It delves into the advantages of breaking down traditional subject boundaries, emphasizing the development of critical thinking skills, real-world problem-solving abilities, and creativity among students. The article also addresses the challenges associated with implementing interdisciplinary education and highlights the importance of collaboration among educators and institutions to prepare students effectively for the complex challenges of the 21st century.